Perioperative Pain Management for Mastectomy in Dogs: A Narrative Review - Giada Giambrone; Giuseppe Catone; Gabriele Marino; Alessandra Sfacteria; Renato Miloro; Cecilia Vullo (Animals)
Mammary tumours are the most common neoplasia in adult female dogs. Mastectomy leads to moderate to severe pain. Effective pain management is crucial in veterinary medicine. This review outlines analgesic techniques for managing perioperative pain in dogs undergoing mastectomy. A literature search on dog mastectomy analgesia was conducted from January 2001 to January 2025. Pre-emptive meloxicam reduces postoperative cardiovascular changes without affecting renal function. When combined with gabapentin, it lowers the need for rescue analgesic opioids, similar to robenacoxib. With regard to tramadol, it offers contrasting analgesia in the studies considered when used alone, while its effect appears enhanced when used in combination with meloxicam/dipyrone. However, methadone provides superior pain control, especially when given preoperatively or intraoperatively. The combination of ketamine, lidocaine, and maropitant enhances pain management, while fentanyl, alone or with lidocaine and ketamine, is effective for intraoperative pain control. Local infiltration with lidocaine/bupivacaine provides effective pain control, and devices like Comfont-in® or WSC facilitate this process. Tumescent anaesthesia using lidocaine/ropivacaine allows for extensive infiltration of the mammary gland. Epidural analgesia, paravertebral blocks, and TAP blocks are beneficial in multimodal protocols. Transdermal patches containing fentanyl/buprenorphine offer prolonged analgesia, while electroacupuncture can help reduce the need for rescue analgesics. Multimodal analgesic protocols are crucial for effective pain management in dog mastectomy surgeries, minimising the need for rescue opioids.